2023
DOI: 10.4103/2045-9912.356473
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen exposure improves functional state of red blood cells in the early postoperative period: a randomized clinical study

Abstract: Molecular hydrogen (H 2 ) has been considered a preventive and therapeutic medical gas in numerous diseases. The study aimed to investigate the potential role of molecular hydrogen as a component of anesthesia in surgical treatment with cardiopulmonary bypass (CPB) of acquired valve defects on the functional state of red blood cells (RBC) and functional indicators of cardiac activity. This clinical trial was conducted with 20 patients referring to the Specialized Cardiosurgical Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recently, a number of randomized clinical studies with inhalation of H 2 gas have been conducted in a variety of diseases. For example, H 2 inhalation improved physical and respiratory function in acute post-COVID-19 patients [ 30 ]; a breathlessness, cough, and sputum scale score in patient with acute exacerbation of chronic obstructive pulmonary disease [ 31 ]; functional state of red blood cells, which is accompanied by a more favorable course of the early postoperative period [ 32 ]; and improved systemic inflammation and liver histology in patients with moderate-severe non-alcoholic fatty liver disease [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of randomized clinical studies with inhalation of H 2 gas have been conducted in a variety of diseases. For example, H 2 inhalation improved physical and respiratory function in acute post-COVID-19 patients [ 30 ]; a breathlessness, cough, and sputum scale score in patient with acute exacerbation of chronic obstructive pulmonary disease [ 31 ]; functional state of red blood cells, which is accompanied by a more favorable course of the early postoperative period [ 32 ]; and improved systemic inflammation and liver histology in patients with moderate-severe non-alcoholic fatty liver disease [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a rapidly increasing amount of research into the physiological effects of consuming hydrogen gas (H 2 ) has identified anti-allergy, anti-inflammatory and antioxidant potentials, which may be relevant for the treatment of numerous human-related diseases and disorders [1][2][3][4][22][23][24]. To assess whether oxyhydrogen would affect the cell viability and proliferation of immortalised immune cells (TK6-B-lymphocytes), this novel enquiry focused on the effects of infusing oxyhydrogen gas into cell culture media in an attempt to simulate the most likely dispersal and retention patterns of the aforementioned gas in the blood or serous fluids.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing body of evidence that both molecular hydrogen (H 2 ) and oxyhydrogen therapies are emerging as effective anti-inflammatory and antioxidant gases [1][2][3][4], which are physiologically well tolerated, as demonstrated in a comprehensive range of clinical trials [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that may protect vascular tissues from damage induced by shear stress and hydroxyl radicals, while preserving the beneficial effects of nitric oxide on vasomotor function. Given that oxidative stress can exacerbate systemic inflammation and thereby impair the function of cardiomyocytes, beta cells, and neurons, as well as endothelium, the potential protective roles of warrant further investigation [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Molecular Hydrogen Therapy For Cardiovascular Diseasesmentioning
confidence: 99%